Simon Birnbaum, Tommy Ferrarini, Kenneth Nelson and Joakim Palme: The Generational Welfare Contract: Justice, Institutions and Outcomes - Steffen Suur-Nuuja; Jörg Tremmel (Intergenerational Justice Review)
No abstract